2013
DOI: 10.3748/wjg.v19.i4.542
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between diversion colitis and quality of life in rectal cancer

Abstract: The severity of DC is related to diarrhea after an ileostomy reversal and may adversely affect QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 23 publications
2
37
0
5
Order By: Relevance
“…This association has been reported previously 35. The pathophysiology is believed to relate to disuse colitis and a prolonged period without restoration of bowel continuity, which may lead to irreversible colon and rectal atrophy 36.…”
Section: Discussionsupporting
confidence: 65%
“…This association has been reported previously 35. The pathophysiology is believed to relate to disuse colitis and a prolonged period without restoration of bowel continuity, which may lead to irreversible colon and rectal atrophy 36.…”
Section: Discussionsupporting
confidence: 65%
“…In bowel neovaginas, inflammatory changes have been related to the deprivation of luminal short‐chain fatty acids after surgical diversion of the faecal stream, a mechanism well known in diversion colitis . Diversion colitis is commonly observed in the remaining distal colonic parts after a colostomy or ileostomy (with a prevalence ranging from 70% to 100%) but may also occur after sigmoid vaginoplasty . Because short‐chain fatty acids play a significant role in the regulation of cellular differentiation and proliferation, it is speculated that short‐chain fatty acid deprivation may lead to an alteration of the cellular environment in favour of the development of colorectal carcinoma …”
Section: Discussionmentioning
confidence: 99%
“…We previously examined the frequency of diversion colitis among Koreans, and we assessed quality of life after ileostomy repair 18. In that study, we found considerable variation in the severity of diversion colitis between patients, and we hypothesized that this variation might be related to differences in the cause of diversion colitis between patients.…”
Section: Introductionmentioning
confidence: 99%